Effect of Downsizing on Work Productivity and Employees Morale in Nepalese Commercial Banks - Bohara, Deepa; Pradhan, Sumit (Nepalese Journal of Management, 2024)
This study examines the effect of downsizing on employee productivity and employee morale in Nepalese commercial banks. Employee productivity and employee morale are the dependent variables. The selected independent variables are training and development, employee motivation, employee engagement, career development opportunities and workload. The primary source of data is used to assess the opinions of the respondents on downsizing and level of productivity and morale in Nepalese commercial banks. The study is based on primary data with 110 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of downsizing on employee productivity and employee morale in Nepalese commercial banks. The study showed that training and development have positive effect on employee productivity and employee morale. This reveals that higher the training and development in the banks, higher would be the employee productivity and employee morale. Similarly, employee motivation has a positive impact on employee productivity and employee morale. This shows that higher the level of motivation in the banks, higher would be the employee productivity and employee morale. Likewise, employee engagement has a positive impact on employee productivity and employee morale. This reveals that increase in employee engagement in the banks leads to increase in employee productivity and employee morale. In addition, career development opportunities have positive effect on employee productivity and employee morale. This reveals that increase in career development opportunities in the banks leads to increase in employee productivity and employee morale. Furthermore, workload has a negative impact on employee productivity and employee morale. It implies that increase in workload in the banks leads to decrease in employee productivity and employee morale.